Development of Digital Teaching Materials on Solo Traditional Cuisine to Increase Cultural Awareness in History Education in Senior High Schools in Surakarta City - Siti Rhohana; Djono Djono; Deny Tri Ardianto (Teknodika, 2025)
History learning is an effort to convey the study of local wisdom in the environment around students. One of the local history studies that can be studied in history lessons is the impact of Dutch colonialism in Indonesia. The impact of Dutch colonialism in Indonesia can be seen in various fields, for example in the cultural sector it can be seen from the development of traditional culinary delights in Solo. This material is compiled in a digital teaching material with the title Solo Traditional Culinary. The aim is to provide cultural basics to students at State High Schools in the City of Surakarta. It is hoped that this digital teaching material will have an impact on teachers and students in the learning process. The approach used in this research is descriptive qualitative. The research locations taken were SMA Negeri 1 Surakarta and SMA Negeri 4 Surakarta. It is hoped that the creation of digital teaching materials can increase cultural awareness and innovation in the development of teaching materials. Apart from that, students are expected to get better learning outcomes by having quality teaching materials.